ETOGRAMA DE LEPTODACTYLUS NATALENSIS LUTZ 1930 (ANURA, LEPTODACTYLIDAE) EM AMBIENTE NATURAL - Santos, Ednilza Maranhão dos; Freire, Eliza Maria Xavier; Amorim, Fabiana Oliveira (Revista Nordestina de Zoologia, 2012)
The objective of this study was to provide an ethogram of Leptodactylus natalensis in natural conditions. Field efforts were effected between two ponds in fragments of Atlantic Forest, in the city of São Lourenço da Mata and in the city of Igarassu . The observations were diurnal and nocturnal and occurred from September/2002 to October/2003, four times each month, with four shifts of sixs hours each (with intervals 30 minutes). A total o thirty nine behavior patterns were recorded and grouped in seven categories: Standing still (6), displacement (6), movement (4), vocalize (4), parental care (10 ) and confrontation (3).